Acute Ischemic Stroke in SARS-CoV, MERS-CoV, SARS-CoV-2: Neurorehabilitation Implications of Inflammation Induced Immunological Responses Affecting Vascular Systems - Karimi, Leila; Sales, Carmela; Crewther, Sheila Gillard; Wijeratne, Tissa (Frontiers in Neurology, 2020)
Coronaviruses (CoVs) are enveloped RNA viruses and have been shown to cause mild to severe respiratory infections in humans, with some severe cases inducing neurological manifestations. The lethality and Neurological effects of the Severe Acute Respiratory Syndrome (SARS-CoV), Middle-East Respiratory Syndrome (MERS-CoV), and recently the Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2) have been well documented though currently there is little literature regarding long term effects and the implications for neurorehabilitation. SARS-CoV-2 and MERS-CoV have been linked to the infection associated inflammatory cytokine storms and induced hypercoagulopathic states that affect the entire vascular system including that of the brain. This mini-review provides an overview of the commonalities among studies published on all three types of the coronavirus related to acute ischemic stroke (AIS). The aim was to elucidate the physiological mechanisms underpinning COVID-2 and to reflect the similarities with the chronic inflammation induced symptoms of AIS that are likely to prove a further challenge for neurorehabilitation clinicians post COVID. In terms of increased incidence of COVID and AIS, it is likely that in depth knowledge of increased thrombotic risk in this population will require appropriate anticoagulation treatment, and other therapeutic interventions as well as neurorehabilitation interventions. Lastly the risk of spreading the virus requires further balancing of the provision of neurorehabiliatation services useful to the patient.